Effect of fixed media on biological wastewater treatment - Mamun, Abdullah Al; Abdul Rahman, Muhammad Amiruddin; Alam, Md. Zahangir; Sayem, Abu S. M; Nedjai, Radhia (IIUM Press, 2022)
Adequate treatment of wastewater is important for the protection of the environment. In many countries, the existing conventional biological wastewater treatment systems are unable to meet the required standards. Therefore, the present research focused on the improvement of aerobic wastewater treatment plants by adding readily available cheap media. Plastic net-like media was used due to its non-biodegradable property. The media length was 5 meters, but it was rolled into a spiral shape. The average removal of TDS and COD, without the media, was about 35% and 70%. After the media has been added, the removal efficiency improved to 55% and 95%. The experimental results demonstrated that the use of media is capable of improving the quality of effluents in wastewater treatment towards a better quality of effluent to be discharged to nature.Such improvements in pollutant removal can be attributed to the retainment of a high amount of microbes in the fixed media, which provided a high surface area compared to a system without any media.